Application of Mudharabah and Wadiah Contracts on iB Dhuha Produk Products Hajj and Umrah Savings Bank Riau Kepri Syariah Capem Duri - Siti Tanjung; Muhammad Yusuf; M Mukhlis (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2018)
This study aims to determine the application of mudharabah and wadiah contracts on IB Dhuha savings and their impact on Bank Riau Kepri Syariah Capem Duri. This research is a qualitative research by describing the research results. This study uses interviews, documentation and observations of sources/research samples totaling 25 people. From the research results, it is known that the mudharabah contract is a contract that uses a profit-sharing system with a minimum initial deposit of Rp. 100,000 and then according to the length of savings, a minimum of 1 year and a maximum of 5 years. After the funds reached Rp. 25,000,000, customers can already get a portion. Of the 10 prospective customers who were offered ib dhuha savings, 6 of them chose ib dhuha hajj savings with a mudharabah contract, this is because the mudharabah contract is not subject to monthly administration fees, the mudharabah contract promises profit sharing and the mudharabah contract deposit has been determined and taken directly from the account general savings for customers so that customers do not have to make special deposits for Hajj savings. and Akad wadi'ah is one of the savings that uses a deposit system, the customer provides an initial deposit of at least Rp. 50,000 and the next deposit is at least Rp. 20,000, customers will be charged a deposit fee every month. With the mudharabah contract, there was a decrease in the opening of Hajj ib Dhuha savings accounts with wadiah contracts, although some customers continued to use wadiah contracts because the wadiah contract was not subject to an account opening fee, the second and subsequent deposits for payment of Hajj savings with wadi'ah contracts were not specified, but according to the ability of the customer and a minimum of Rp. 20,000, Funds deposited will not be used by the bank for any activities, purely only deposited so that customers will not be afraid of their funds being used for bad things, customer funds can be withdrawn at any time and customers can determine their own departure time, there is no specific time period . With the increasing choice of types of contracts in the iB Dhuha hajj savings account at the Riau Kepri Syariah Capem Duri bank, making the public's interest higher to open hajj savings at the Riau Kepri Syariah capem Duri bank, this is known from the increasing number of ib Dhuha hajj savings customers at the Riau Kepri Syariah bank. capem Duri.